2017
DOI: 10.1016/j.icheatmasstransfer.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and model development for thermal conductivity of α-Al2O3-glycerol nanofluids

Abstract: A B S T R A C TIn order to investigate the effect of nanoparticle volume fraction, nanoparticle size and temperature on the thermal conductivity of glycerol based alumina (α-Al 2 O 3 ) nanofluids, a set of experiments were carried out for temperature ranging from 20°C to 45°C. The nanofluids contained α-Al 2 O 3 nanoparticles of three different sizes (31 nm, 55 nm and 134 nm) were prepared by two-step method at volume fractions ranging from 0.5% to 4%. The experimental results show that α-Al 2 O 3 -glycerol na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…It can be observed that the nanofluid viscosity increases with the volume concentration. Previous studies [27][28][29][30][31][32][33] reported similar results for the viscosities and thermal conductivities of nanofluids. The density and specific heat of the nanofluid were calculated using the following mixing theory equations:…”
Section: Thermophysical Properties Of Nanofluidssupporting
confidence: 72%
“…It can be observed that the nanofluid viscosity increases with the volume concentration. Previous studies [27][28][29][30][31][32][33] reported similar results for the viscosities and thermal conductivities of nanofluids. The density and specific heat of the nanofluid were calculated using the following mixing theory equations:…”
Section: Thermophysical Properties Of Nanofluidssupporting
confidence: 72%
“…It was suggested that this increase was caused by the increased interfacial area between nanoparticles and base liquid for smaller particle sizes. Using the same method, Sharifpur et al [42] studied the thermal conductivity of Al 2 O 3 -glycerol nanofluid. Experiments were conducted using Al 2 O 3 nanoparticles of three different diameters, including 31 nm, 55 nm, and 134 nm.…”
Section: Effects Of Nanoparticle Size On Nanofluid Thermal Conductivitymentioning
confidence: 99%
“…It was suggested that this increase was caused by increased Brownian motion at higher temperatures. However, several researchers have suggested that the effect of temperature on the thermal conductivity of nanofluids is solely a result of the increase in thermal conductivity of the base liquid [15,26,42]. Using the transient short hot-wire method, Yu et al [15] measured the thermal conductivities of AIN-Ethylene Glycol and AIN-propylene glycol nanofluids within the temperature range on 10-60 • C. A negligible change in thermal conductivity with the increase of temperature was observed.…”
Section: Effects Of Temperature On Nanofluid Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of nanofluids is one of the important parameters to achieve nanoparticle stability in a suspension [17]. Most of the modelling of the properties of nanofluids in the literature is limited to thermal conductivity and viscosity of nanofluids [16,[18][19][20][21][22][23][24][25][26][27], and there is a lack of modelling for other properties such as pH and electrical conductivities. An adaptive neuro-fuzzy inference system (ANFIS) and genetic algorithm polynomial neural networks (GA-PNN) are two novel approaches that use the advantages of neural network, fuzzy logic and genetic algorithm (GA) methods for modelling the effective pH and the electrical conductivity of magnesium oxide-ethylene glycol (MgO-EG) nanofluids.…”
Section: Introductionmentioning
confidence: 99%